Pre and post introduction of pneumococcal conjugate vaccines in children in Eastern Mediterranean Region and effect on antimicrobial resistance, a narrative review - Saleh, Basma M.; Mere, Osama; Elmrayed, Seham (Frontiers in Microbiology, 2026)
BackgroundAntimicrobial resistance (AMR) is a pressing public health challenge in the Eastern Mediterranean Region (EMR), with Streptococcus pneumoniae being a major contributor due to its role in invasive pneumococcal disease (IPD). Pneumococcal conjugate vaccines (PCVs) have shown promise in reducing vaccine-type IPD and AMR, yet significant barriers persist.ObjectiveThis review examines the impact of PCVs on AMR, serotype distribution, and vaccine coverage in pediatric populations within the EMR, emphasizing the interplay between vaccination strategies and AMR trends.ContentThe introduction of PCVs, particularly PCV13, has led to reductions in vaccine-type IPD and AMR in several EMR countries. For example, post-PCV13 penicillin susceptibility in Saudi Arabia improved from 37 to 100% in invasive isolates, and Lebanon reported significant reductions in vaccine-type AMR. However, challenges such as inconsistent vaccination coverage (e.g., 76% in Yemen, absent in Egypt), socio-political instability, and the emergence of non-vaccine serotypes (NVTs) as per shown in the 73.5% of isolates in Omani children and the high multidrug resistance (MDR) rates (e.g., 85.7% in Yemen) undermine these benefits. Serotype replacement phenomena, driven by ecological shifts, are increasingly contributing to disease burden and AMR. While PCVs reduce the need for antibiotics and limit selective pressures driving resistance, high rates of MDR and inadequate antibiotic stewardship remain concerns. Strengthened vaccination programs, high-valency vaccines, and robust surveillance systems are critical to addressing these challenges.ConclusionPCVs play a pivotal role in mitigating AMR and reducing pneumococcal disease burden in the EMR. However, suboptimal vaccine coverage, NVT emergence, and persistent AMR highlight the need for comprehensive strategies, including enhanced coverage of higher valency vaccines, robust surveillance, targeted public health interventions, strengthened antibiotic stewardship, and improved regional collaboration. Addressing these issues can significantly reduce the AMR burden and improve health outcomes across the region.